Advertising Effectiveness on Brand Judgment and Consumer Preference in Purchasing Decision in Pakistan - Latif, Abdul; Syed, Anwar Ali Shah G; Halepoto, Ali Hassan; Nazar, Muhammad Suhail; Shaikh, Faiz M (Journal of Asian Business Strategy, 2012)
The research investigates the advertising effectiveness on brand judgment and consumer preferences in Pakistan. Advertising is often seen as an efficient but sometimes ineffective external influence on buyer behavior in making the purchase decision. Marketers are therefore seeking ways to make advertising more effective. This paper provides a theoretical framework explaining how advertisements (ads) can influence attitude and purchase intentions by activating an identity with one’s gender group to influence purchase decision in both gender groups. A gender group identity is an example of a social identity in which one sees oneself as a member of his or her gender group. Data were collected from 400 respondents by using the simple random technique; Structured Questionnaire was developed to get reliable results. The response rate was 90% in urban areas and 70% in rural areas; 80 percent of the respondents were male and 20% were female. This paper posits that favorable outcomes may be carried over to associated ads and brand judgments. This paper has also aligned social identity theory with the integrated tradition of understanding gender. The results show that advertising has positive impact on brand judgment, preferences among various brands in purchase decision, and behaviors consistent with group norms triggering an in-group bias. The readiness or ease with which a gender group identity becomes salient may depend on how strongly a person identifies with one’s gender group. In this paper, it is argued that ads that activate identification with one’s gender group will have a more favorable impact on future brand and ad judgments than ads that do not activate this identity. The study draws from three areas of the literature to support the propositions: advertising effectiveness; brand judgment; and consumer preferences. The study reveals that advertising has positive impact on brand judgment in respect of purchase decision in Pakistan.